2019
DOI: 10.1155/2019/2946713
|View full text |Cite
|
Sign up to set email alerts
|

Taenia crassiceps-Excreted/Secreted Products Induce a Defined MicroRNA Profile that Modulates Inflammatory Properties of Macrophages

Abstract: Helminth parasites modulate immune responses in their host to prevent their elimination and to establish chronic infections. Our previous studies indicate that Taenia crassiceps-excreted/secreted antigens (TcES) downregulate inflammatory responses in rodent models of autoimmune diseases, by promoting the generation of alternatively activated-like macrophages (M2) in vivo. However, the molecular mechanisms triggered by TcES that modulate macrophage polarization and inflammatory response remain unclear. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…Data showed that compared with the control group, BMDMs showed long fusiform shape in the LPS-treated group ( Figure 1B). Moreover, the expression levels of related factors including IL-1b, IL-6, IL-12 and TNF-a, as well as INOS, were significantly increased in the LPS-treated group in a dose-dependent manner ( Figure 1C, p < 0.05), which was consistent with previous reports, [30][31][32] indicating the activation of TLR4 signalling. Notably, we found that the expression level of miR-7 in BMDMs was significantly up-regulated in a dose-and time-dependent manner, and reached a peak in the presence of 100 ng/ml LPS at 12 h ( Figure 1D,E, p < 0.05).…”
Section: The Expression Of Mir-7 Is Up-regulated During Tlr4 Signallisupporting
confidence: 92%
“…Data showed that compared with the control group, BMDMs showed long fusiform shape in the LPS-treated group ( Figure 1B). Moreover, the expression levels of related factors including IL-1b, IL-6, IL-12 and TNF-a, as well as INOS, were significantly increased in the LPS-treated group in a dose-dependent manner ( Figure 1C, p < 0.05), which was consistent with previous reports, [30][31][32] indicating the activation of TLR4 signalling. Notably, we found that the expression level of miR-7 in BMDMs was significantly up-regulated in a dose-and time-dependent manner, and reached a peak in the presence of 100 ng/ml LPS at 12 h ( Figure 1D,E, p < 0.05).…”
Section: The Expression Of Mir-7 Is Up-regulated During Tlr4 Signallisupporting
confidence: 92%
“…As the infection progressed, PEC/macrophages from infected mice also showed an impairment of their ability to secrete NO in response to LPS compared to PEC obtained during the early phase of infection ( rst week). Although M. vogae-derived products induce the expression of markers of alternative activation (YM1, Arg-1 and Fizz-1) in vivo and in vitro [4], it is likely that the parasite ES antigens play important role in regulating cytokine production by inhibiting their transcripts, as has been previously reported [37].…”
Section: Discussionmentioning
confidence: 66%
“…As the infection progressed, PEC/macrophages from infected mice also showed an impairment of their ability to secrete NO in response to LPS compared to PEC obtained during the early phase of infection (first week). Although M. vogae -derived products induce the expression of markers of alternative activation (YM1, Arg-1 and Fizz-1) in vivo and in vitro [ 4 ], it is likely that the parasite ES antigens play important role in regulating cytokine production by inhibiting their transcripts, as has been previously reported [ 37 ].…”
Section: Discussionmentioning
confidence: 99%